Risk of prostate cancer in patients with inflammatory bowel disease: a nationwide cohort study in South Korea - Ji Eun Na; Tae Jun Kim; Yeong Chan Lee; Ji Eun Kim; Eun Ran Kim; Sung Noh Hong; Dong Kyung Chang; Young-Ho Kim (Therapeutic Advances in Gastroenterology, 2022)
Background: Several studies have suggested an association between inflammatory bowel disease (IBD) and the risk of prostate cancer development. However, these findings are inconsistent, and studies based on Asian populations are limited. Objectives: We compared the risk of prostate cancer according to IBD status using the Korean National Health Insurance Service database. Design: A population-based retrospective cohort of age-matched 59,044 non-IBD patients and 14,761 IBD patients between January 2009 and December 2011 was analyzed up to December 2017. Methods: The risk of prostate cancer was compared between patients with IBD and controls using the Cox proportional hazards regression model and Kaplan-Meier survival analysis. Results: During a median follow-up of 6 years, the incidence rate of prostate cancer was 264 per 100,000 person-years in non-IBD patients and 242 per 100,000 person-years in patients with IBD. IBD status was not associated with the risk of prostate cancer compared to non-IBD [adjusted hazard ratio (aHR) 0.93, 95% confidence interval (CI): 0.80–1.08, p  = 0.32). The cumulative incidence of prostate cancer did not differ by IBD status (non-IBD patients versus IBD patients: log-rank p  = 0.27; non-IBD patients versus ulcerative colitis versus Crohn’s disease: log-rank p  = 0.42). In multivariate analysis, age was an independent risk factor for the development of prostate cancer (HR 1.03, 95% CI: 1.02–1.03, p  < 0.001). Conclusion: In our population-based study, IBD status was not associated with the risk of prostate cancer.